Exponentially tapered H-tree clock distribution networks. - El-Moursy, M.A.
Exponentially tapered interconnect can reduce the dynamic power dissipation of clock distribution networks. A criterion for sizing H-tree clock networks is proposed. The technique reduces the power dissipated for an example clock network by up to 15% while preserving the signal transition times and propagation delays. Furthermore, the inductive behavior of the interconnects is reduced, decreasing the inductive noise. Exponentially tapered interconnects decrease by approximately 35% the difference between the overshoots in the signal at the input of a tree. As compared to a uniform tree with the same area overhead, overshoots in the signal waveform at the source of the tree are reduced by 40%.
Keywords: H-tree clock network; Clock distribution network; Dynamic power dissipation; Inductive noise; Propagation delay; Signal transition time; Signal waveform; Tapered interconnect